P-428 Fertility outcomes following treatment of chronic endometritis: a systematic review and meta-analysis. (30th June 2022) - Dhatt, A; Rozon, C; Gale, J; Wu, C
Abstract: Study question: To determine if treatment of chronic endometritis (CE) impacts fertility outcomes Summary answer: Treatment of CE in women with infertility, recurrent pregnancy loss, or recurrent implantation failure, improves live birth outcomes What is known already: Chronic endometritis is an inflammatory condition that involves plasma cells invading the endometrial stroma. Prevalence of CE is high among patients with recurrent pregnancy loss (RPL), recurrent implantation failure (RIF), and infertility. Proposed treatment strategies include oral antibiotics, intrauterine antibiotic infusion, platelet-rich plasma, and hysteroscopic surgery, among others. Although treatment-associated CE cure rates have been high, few studies have reported on fertility outcomes following treatment of CE. Previously published systematic reviews have also yielded widely conflicting outcomes regarding the impact of CE treatment on fertility outcomes. Study design, size, duration: We conducted a systematic search of the literature until late December 2021 across the Cochrane, EMBASE, and Medline databases. We used a DerSimonian and Laird random-effects meta-analysis model for the quantitative analysis. Participants/materials, setting, methods: Clinical trials, prospective and retrospective observational studies that examined the treatment outcomes of CE were included. Study eligibility assessment, data extraction, and risk of bias assessment were independently performed by two reviewers. Comparisons were made between the groups of treated versus untreated CE, treated versus persistent CE, and between specific treatment strategies. Pooled risk ratios (RR) for the impact of CE treatment on outcomes such as live birth, clinical pregnancy, and miscarriage rates were assessed Main results and the role of chance: Twelve studies totalling 1, 539 women were included in our systematic review (3 randomized controlled trials and 9 observational studies), and 5 studies were included in the quantitative meta-analysis. Patients all had confirmed CE and a history of infertility, RPL, or RIF. Cure rates ranged between 37.2-91.8%. Live birth rate in the treated CE group ranged from 27.1-84.6%, from 16.4-44.4% in the non-treated CE group, and from 6.7-30.8% in the persistent CE group. Clinical pregnancy rate in the treated CE group ranged from 29.3-76.3%, from 11.1-30% in the non-treated CE group, and from 20-42.3% in the persistent CE group. Miscarriage rate in the treated CE group ranged from 6.7-23.8%, from 35.7-55.6% in the non-treated CE group, and from 27.3-66.7% in the persistent CE group. Risk ratio for the pooled effect of successful CE treatment compared to persistent CE on live birth was 2.98 (95% confidence ratio [CI] 1.51-5.91, I2=36.8%), on clinical pregnancy rate was 2.25 (95% CI 1.59-3.18, I2=40.1%), and on miscarriage rate was 0.55 (95% CI 0.28-1.10, I2=0.0%). Insufficient studies compared specific treatment subtypes to allow for any substantive qualitative or quantitative analysis. Limitations, reasons for caution: Our results are limited by significant between-study heterogeneity in the study design, patient population, and comparisons used. Subgroup analysis by categories of comparisons mitigates some of this heterogeneity Wider implications of the findings: Adequate treatment of CE significantly improves live birth rates in patients with RPL, RIF, and infertility. Assessment for CE should become part of routine fertility investigations, and resolution of CE must be confirmed prior to initiating fertility treatments. Trial registration number: not applicable